Sonographic differential diagnosis of duplex kidneys - Deeg, Karl-Heinz (Ultraschall in der Medizin, 2022)
Duplex kidneys have two renal pelvises and two ureters, which can join on the way to the urinary bladder but can also enter the bladder separately. A distinction must be made between normal and pathological duplex kidneys. In normal duplex kidneys, both renal pelvises are normal in width, and the upper and lower poles are approximately the same size. Furthermore, ureters are not dilated, and the upper and lower poles of the kidneys are not cystically altered. In contrast, pathological duplex kidneys, occurring in about 50 % of cases, are characterized by dilation of one or both renal pelvises. Additionally, one or both ureters may be dilated. Megaureters may be obstructive or refluxive. If a megaureter is present, a ureterocele must be ruled out, as well as an ectopically opening ureter. A pathological duplex kidney must always be assumed if one pole of the kidney is hypoplastic. Hypoplasia of the upper renal pole is often associated with an obstructive megaureter. Vesicoureteral reflux into the lower pyelon is common in hypoplasia of the lower pole. In the presence of vesicoureteral reflux, the associated (lower) pyelon is dilated when the bladder is full or during micturition. In addition, there is a dilated ureter. On the other hand, the pyelon can have a normal width when the bladder is empty. In rare cases, one pole may be cystically altered in pathological duplex kidneys. In this instance, segmental multicystic dysplastic duplex kidney must be differentiated from segmental multicystic nephroma.
CRIS-Team WoS Importer:2022-05-13